Ex vivo-model design and evaluation of the sensitivity of blast cells to chemotherapy as a way to personalize the treatment of acute myeloid leukemia - A. S. Polyakov; Ya. A. Noskov; Yu. V. Nikitin; V. V. Tyrenko; S. N. Kolubaeva; A. N. Bogdanov; V. N. Semelev; O. R. Petrova; S. V. Bondarchuk; D. K. Zhogolev; A. D. Zolotarev; A. V. Kovalev; et al. (Онкогематология)
Despite continuous attempts to improve therapy, the outcomes of acute myeloid leukemia remain almost unchanged over last decades. Drugs made with a more complete understanding of the biology of acute myeloid leukemia do not equal the hopes for better prognosis. The best results are achieved only with high-dose chemotherapy, which is only possible for a limited number of patients. High phenotypic and genotypic heterogeneity of acute myeloid leukemia defines the relevance to develop personalized approaches to therapy, including those based on determination of individual drug sensitivity of blast cells.This article presents the results of developing an ex-vivo model of acute myeloid leukemia, as well as testing of two in vitro sensitivity assessment methods: evaluation of the genotoxicity of drugs in the micronucleus test and vitality and sensitivity to chemotherapy in sorted blast cells. Prospects of individualized therapy of acute myeloid leukemia were determined based on introduction into clinical practice and continuing the research.